Expectations, professional competences, and the role of physical education teachers in a historical perspective - Ławniczak, Paweł (Physical education, sport and olympism from a pedagogical perspective, 2023)
The study is focused on the physical education teacher, it contains information on the teaching profession in the specialty of physical education as well as the figure of the physical tutor present in the literature on the subject in the field of pedeutology and physical culture. More important information has been collected in the form of studies and research results about the physical education teacher created over a hundred years of the real functioning of this topic in the literature. The author used his own studies in this area contained in several articles found in the post-conference materials. They contain reflections and comments on four main areas of concern. The first one focuses on the history of the formation of the specialty of physical education and the formulation of reflections on the specialist teacher. The second covers the topic of competencies and qualifications required in the profession of physical tutor, which is the most widely present in the literature, including the discussion about authority and its sources. The third concerns the widely understood and changing conditions of the work of a physical tutor and the consequences for the teacher and the process itself. In the final part of the article a historical review of initiatives and institutions for educating physical educators was presented.